Embryo survival in lactating dairy cows - J.A. Carmill; S.E. Zarkouny; B.A. Hensley; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2000)
Rates of embryo survival in lactating dairy cows were assessed in three separate studies. Based on pregnancy diagnoses 27 to 29 days after timed inseminations, survival to days 40 to 50 or day 57, depending on the study, varied from 9 to 88% in cows that were not cycling before insemination compared to 57 to 90% in cows that were cycling. Previously anestrous cows had lower rates of survival. In one study, supplementing cows with progesterone before insemination improved embryo survival.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Embryo survival; Cows; First AI